Hybrid resection of large colorectal adenomas combining EMR and FTRD. (3rd August 2021) - Bauermeister, Maximilian; Mende, Matthias; Hornoff, Steffen; Faiss, Siegbert
Abstract: Background: The introduction of the full-thickness resection device (FTRD) allowed resection of difficult adenomas in the duodenum and colorectum with non-lifting. The main limitation of this endoscopic technique is the lesion size. We describe a hybrid approach combining endoscopic mucosal resection (EMR) and FTRD in a cohort of 17 patients to reduce tumor size and enable full-thickness resection. Methods: Retrospective analysis from data of 17 patients who underwent hybrid EMR-FTRD for large adenomas in the colorectum at our institution. Technical success, histological confirmation of margin-free resection and adverse advents were studied. Results: 16 of 17 (94.1%) lesions could be resected macroscopically complete with confirmed full-thickness resection. Histological work-up of the full-thickness specimens showed free lateral margins in 13 patients (76.4%), unclear margins in two patients (11.8%) and positive margins in two patients (11.8%). There were no immediate perforation or major bleeding, however one patient showed a stenosis after resection in the follow-up endoscopy. Follow-up endoscopy was available in 12 patients. In two of 12 patients a recurrent adenoma was detected. Conclusions: Hybrid EMR–EFTR in the colorectum seems to be a safe and effective technique for large non-lifting lesions with positive lifting signs in the margins. Further prospective evaluation of efficacy, safety and long-term outcome of this hybrid technique is necessary.